Municipal reform - Dougherty, Bradford (My University, 1896)
Introduction: The subject of municipal reform is one of world wide interest at the present time. All over this and foreign countries in all cities and especially the larger ones, there is some movement on foot for the bettering of the public affairs in the city. It seems to be a time of moral awakening when many of the forces are putting their best efforts forth for the advancement of right in political affairs.
Citation: Dougherty, Bradford. Municipal reform. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Municiple reform; Public affairs; Political affairs; Morals; Theses; Manuscripts (documents)